MEMBUMIKAN “DEKLARASI KAIRO” DI INDONESIA: Perlindungan Terhadap Hak Anak dan Keluarga - Agus Dedi Putrawan (TASÂMUH, 2016)
It has become a world agreement and part of Indonesian constitution, the position of human rights in the Islamic discourse is still debatable. Pros and cons are still going on, especially in the matter of right to freedom of religion and belief, including the right to get out of religion and the right not to be religious. Right to freely choose a partner including the right to mate with other religions and the right for same sex couple marriage, and the right to life. Bringing human rights in Indonesia is not as easy as turning the palm of the hand since human rights in Indonesia are very complex and law is still not able to provide protection to victims of human rights, concepts and standardization, the media does not support the proclamation of human rights, public services have not been optimal, customs sometimes legalized violence, poverty issues and erroneous interpretation of religious teachings. These were all wrapped up in a patriarchal culture. This paper will discuss more on Cairo Declaration, specifically article 7 (on the rights of children and families) and the things associated with it. Cairo Declaration, article 7 consists of: 1) At birth, every child has the right of parents, communities and countries to be given the maintenance, care and education materials, health and morals. The fetus and the mother must also be kept and given special attention. 2) The parents and that such capacity they have the right to choose the kind of education they want for their children, provided that they take into consideration the interests and future of the children in accordance with ethical values and Sharia. 3) Both parents have certain rights from their children, and relatives have rights of their relatives, in accordance with Sharia.